2017
DOI: 10.1007/s11999-017-5474-7
|View full text |Cite
|
Sign up to set email alerts
|

Are Barbed Sutures Associated With 90-day Reoperation Rates After Primary TKA?

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Our results also showed uneventful wound healing response without the incidence of wound complications, such as surgical site infections and reoperation, in both groups during the 6-month followup period. These ndings were comparable to the previous studies [2,27], which implied that either the CLS or IHM techniques with traditional braided suture materials are safe. Moreover, the previous studies demonstrated that using barbed suture for super cial wound closure in TKR might be associated with higher risk for wound complications [3,5,20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results also showed uneventful wound healing response without the incidence of wound complications, such as surgical site infections and reoperation, in both groups during the 6-month followup period. These ndings were comparable to the previous studies [2,27], which implied that either the CLS or IHM techniques with traditional braided suture materials are safe. Moreover, the previous studies demonstrated that using barbed suture for super cial wound closure in TKR might be associated with higher risk for wound complications [3,5,20].…”
Section: Discussionsupporting
confidence: 88%
“…As an improvement over the interrupted technique, an innovated barbed knotless suture has recently been introduced for the continuous running suture technique, and it has a demonstrated ability to facilitate comparatively faster wound closure time, superior watertight closure, and potentially minor cost reduction [10,19,30]. Notably, though, a few studies have reported an association between the barbed suture and some postoperative complications, such as surgical site infection [20], extensor mechanism repair failure [27], and possible higher risk of reoperation [2]. To the best of our knowledge, the evidence for the optimal wound closure has not been clearly developed [12], and the data related to the postoperative outcomes after using other simple suture techniques, such as continuous locking suture (CLS) with braided suture for arthrotomy repair in TKR, has never been published.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have investigated use of barbed sutures for laparoscopic procedures [ 6 , 9 , 19 ], suturing viscus [ 5 , 7 , 11 , 16 21 ] or the deep layers in arthrotomy [ 12 , 22 , 23 ], fewer have assessed KBS in dermal, subcutaneous, and subcuticular closure. Some studies on knee and hip arthroplasty in humans found increased complication rates (infection, dehiscence) when KBS was used to close superficial tissue layers [ 12 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many analyzed wound complications for knotless barbed suture compared to standard absorbable suture for skin closure with mixed results in prospective randomized control trials despite a universal reduction in closure time [7][8][9][10][11][12][13][14] . In a prospective randomized control trial by Khan, et al, the Dermabond skin closure group showed less drainage within the first 24 hours but more overall in follow-up when compared to monocryl suture 15 .…”
Section: Discussionmentioning
confidence: 98%